“I am still human and worth a life:” a qualitative study of the impacts of a community based, peer-led, treatment support model for young adults living with HIV in Zimbabwe - Zamudio-Haas, Sophia; Mahaka, Imelda; Chapwanya, Gwendoline; Dunbar, Megan S.; Lightfoot, Marguerita (Frontiers in Public Health, 2024)
Background A persistent treatment gap remains between children and adults living with HIV. The Zvandiri program, developed by Africaid, is one of the few models of differentiated service delivery for children, adolescents, and youth that has been shown to improve outcomes along the HIV care continuum, employing Community Adolescent Treatment Supporters (CATS) to offer peer counseling and patient navigation. Our qualitative study provides an in-depth analysis of the feelings and experiences Zimbabwean youth had following an HIV diagnosis, and the ways that CATS facilitated linkage and retention in care. Methods We conducted in-depth interviews in Shona with adolescents and young adults who were recently diagnosed with HIV in Zimbabwe. Interviews were audio-recorded, transcribed, and then translated to English. Interviews were coded in Dedoose using a structured a priori codebook. We wrote semi-structured summary memos for each interview. We co-conducted thematic analysis, guided by interpretive phenomenology with a team of Zimbabwean and American experienced qualitative researchers and community partners. We co-developed memos to elaborate and understand key themes across interviews. Results Most of our interview participants recounted an immediate sense of loss upon testing HIV positive and a fear that “there was no hope for the future.” CATS played a pivotal role for youth, providing emotional, educational, and logistical support to facilitate treatment initiation, adherence, and persistence in care. The CATS program supported youth through multiple approaches: group sessions, individual meetings, and via text or phone. While CATS offered counseling and comfort to participants, they emphasized the long-term importance of identifying at least one other person in participants’ lives who could know their status and support them around HIV. Conclusion Our findings delineate some of the key concerns that face youth after receiving an HIV diagnosis and the ways that a community-based adherence peer navigation program supported participants to navigate both their feelings and the health care system. Results can inform practice at community-based agencies that are implementing or considering peer youth navigation programs and garner support for policy to fund interventions for youth.